Medium Term Outcomes of Deep Venous Stenting in the Management of Venous Thoracic Outlet Syndrome. (December 2022) - de Boer, Madeleine; Shiraev, Timothy; Saha, Prakash; Dubenec, Steven
Abstract : Objective: Venous thoracic outlet syndrome (vTOS) is a relatively rare condition associated with significant morbidity. Its management continues to evolve, with increasing use of endovascular adjuncts, such as percutaneous thrombectomy and angioplasty, in addition to first rib resection. The utility of stenting residual venous stenotic lesions is poorly defined within the literature. This study sought to review the medium term patency rates of upper limb deep venous stenting in the management of vTOS. Methods: A single centre, retrospective review of patients managed for vTOS with first rib resection followed by upper limb deep venous stenting between January 2012 and February 2021 was conducted. Post-procedural ultrasounds were reviewed to determine stent patency. Results: Twenty-six patients were included, with 33 stents placed. The median duration of follow up was 50 months. On venous duplex ultrasound at three years post-operatively, primary patency rates were 66%, primary assisted patency rates were 88%, secondary patency rates were 91%, and total occlusion rates were 9%. After stent placement, 80% of patients remained asymptomatic with regard to compression symptoms. Conclusion: Upper limb deep venous stenting is an effective adjunct to surgical decompression in the management of vTOS. Stent medium term patency rates are promising; however, further studies with longer follow up and larger cohorts with multicentre results are required to confirm these early findings.